Cytoprotective-selective activated protein C therapy for ischaemic stroke - Mosnier, Laurent O.; Zlokovic, Berislav V.; Griffin, John H. (Thrombosis and Haemostasis, 2014)
Despite years of research and efforts to translate stroke research to clinical therapy, ischaemic stroke remains a major cause of death, disability, and diminished quality of life. Primary and secondary preventive measures combined with improved quality of care have made significant progress. However, no novel drug for ischaemic stroke therapy has been approved in the past decade. Numerous studies have shown beneficial effects of activated protein C (APC) in rodent stroke models. In addition to its natural anticoagulant functions, APC conveys multiple direct cytoprotective effects on many different cell types that involve multiple receptors including protease activated receptor (PAR) 1, PAR3, and the endothelial protein C receptor (EPCR). Application of molecular engineered APC variants with altered selectivity profiles to rodent stroke models demonstrated that the beneficial effects of APC primarily require its cytoprotective activities but not its anticoagulant activities. Extensive basic, preclinical, and clinical research provided a compelling rationale based on strong evidence for translation of APC therapy that has led to the clinical development of the cytoprotectiveselective APC variant, 3K3A-APC, for ischaemic stroke. Recent identification of non-canonical PAR1 and PAR3 activation by APC that give rise to novel tethered-ligands capable of inducing biased cytoprotective signalling as opposed to the canonical signalling provides a mechanistic explanation for how APC-mediated PAR activation can selectively induce cytoprotective signalling pathways. Collectively, these paradigm-shifting discoveries provide detailed insights into the receptor targets and the molecular mechanisms for neuroprotection by cytoprotective-selective 3K3A-APC, which is currently a biologic drug in clinical trials for ischaemic stroke.
Keywords: Stroke; activated protein C; PAR1; PAR3; EPCR